Implementation of discussion methods to increase indonesian language students’ achievement at the sixth grade students in sdn. 03 perawang barat in academic year 2014/2015 - Netti Yarni (Fakultas Sastra Universitas Ekasakti, 2017)
In general, Indonesian lessons in the eyes of easy and considered trivial by students and even teachers themselves. This view has many implications for the less treatment of Indonesian subjects, making them less profitable for the development of the learning process and causing problems. This condition has an impact on the low student's daily test score, with an average of 55 so as not to achieve the completeness of learning (KKM) that has been implemented school 75. Therefore required a research action that aims to improve the learning process and improve learning outcomes by using Discussion methods. The formulation of the research are: